Investigation on mechanical properties of heat treated low carbon steel - Abd Hisham, Mohamad (2008)
The heat treatment method was used in early 1000 B.0 when the artifact of crude iron was found. Heat treatment is a method used to alter the physical, and sometimes chemical, properties of a material usually ductility, hardness, yield strength, and impact resistance. Heat treatment involves the use of heating or chilling, normally to extreme temperatures, to achieve a desired result such as hardening or softening of a material.. There are many types of furnace are used for heat treating but the basic types of furnace are batch furnace and continuous furnace. Selection of .a material for specific application required a full understanding of its mechanical properties including tensile properties, elastic and plastic behavior, brittle fracture, strength and hardness. The purpose of this study is to obtain the most optimum value of UTS (ultimate tensile strength), Y (yield strength) and strain by using suitable heat treatment method such as quenching, hardening and tempering. After heat treatment process, these metals were test using tensile test machine to investigate the mechanical properties. Evaluation was based on the value of UTS (ultimate tensile strength), Y (yield strength) and strain. It was found out that the annealing process was the best method of heat treatment to produce the most optimum value of UTS (ultimate tensile strength), Y (yield strength) and strain. The finding suggest that there are should used other method of heat-treatment such as case hardening, carbon nitriding and so on to understand more about mechanical properties of low carbon steel or mild steel and how to change the microstructures in metal or to improve the mechanical properties of mild steel.